VRK1 Predicts Poor Prognosis and Promotes Bladder Cancer Growth and Metastasis In Vitro and In Vivo - Jiacheng Wu; Tao Li; Hao Ji; Zhi Chen; Baoqian Zhai (Frontiers Media S.A., 2022)
Bladder cancer (BC) is one of the most common malignant tumors in the urinary system with growing morbidity and diagnostic rate in recent years. Therefore, identifying new molecular biomarkers that inhibit the progression of bladder cancer is needed for developing further therapeutics. This study found a new potential treatment target: vaccinia-related kinase 1 (VRK1) and explored the function and mechanism of VRK1 in the development of bladder cancer. First, TCGA database and tissue microarray analysis showed that VRK1 was significantly upregulated in bladder cancer. Kaplan-Meier survival analysis indicates that the OS and PFS of the VRK1 high expression group were significantly lower than the VRK1 low expression group (p = 0.002, p = 0.005). Cox multi-factor analysis results show that VRK1 expression is an independent risk factor affecting tumor progress. The maximum tumor diameter, staging, and adjuvant chemotherapy also have a certain impact on tumor progression (p < 0.05). In internal validation, the column C index is 0.841 (95% CI, 0.803-0.880). In addition, cell functional studies have shown that VRK1 can significantly inhibit the proliferation, migration, and invasiveness of bladder cancer cells. In vivo, nude mice transplanted tumors further prove that low VRK1 can significantly inhibit the proliferation capacity of bladder cancer cells. In summary, VRK1 expression is significantly related to the staging, grade, and poor prognosis of patients with bladder cancer. At the same time, in vivo and in vitro experiments have shown that downregulation of VRK1 can significantly inhibit the proliferation of bladder cancer cells. These findings provide a basis for using VRK1 as a potential therapeutic target for patients with bladder cancer.